An Experimental Study on the Socketed Pile in Soft Rock - Maralapalle, V.; Hegde, R. A. (Engineering, Technology & Applied Science Research, 2022)
Pile foundation systems are used in India in many projects such as metro and railways, flyovers, and multi-story buildings. The pile transfers superstructure load to the substructure, i.e. to rock layers by means of skin resistance and end-bearing resistance. In this study, an attempt is made to observe the performance of socketed piles in soft rock. A series of socketed small-scale model pile load laboratory studies have been conducted using the loading frame. Load tests were performed on a model steel pile to calculate its axial load-bearing capability at various socket depths. An unconfined compression test was performed on pseudo-rock variations to find out the properties of the soft rock used. The results showed the ability of the drilled pile to enhance the strength of the pseudo rock. An attempt was also made to calculate the optimum depth for the socketed pile in soft rock.